2018
DOI: 10.1515/sjecr-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits and Standard Body Parameters Among Students at University of Banja Luka

Abstract: Poor dietary habits have become one of the most important concerns among public health policy makers in recent years, due to the impact they have on both economic and health systems of a country. The transitional period toward young adulthood, marked with high school graduation and the beginning of college years, has been identified as critical in terms of its influence on young people’s bad eating habits. The aim of this study was to assess whether the results obtained through Food Frequency Questionnaire sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
(51 reference statements)
2
1
0
Order By: Relevance
“…Some study results showed that meat, milk, nuts and legumes were consumed in lower quantities (El Sayed et al, 2015;Olatona et al, 2018). In a study by Rašeta et al (2018), meat and milk consumption levels were similar to those found in our study (Rašeta et al, 2018). The literature showed that the proportion of students consuming processed foods was quite high and supported our study findings (Bagordo et al, 2013;El Ansari et al, 2015;Abraham et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Some study results showed that meat, milk, nuts and legumes were consumed in lower quantities (El Sayed et al, 2015;Olatona et al, 2018). In a study by Rašeta et al (2018), meat and milk consumption levels were similar to those found in our study (Rašeta et al, 2018). The literature showed that the proportion of students consuming processed foods was quite high and supported our study findings (Bagordo et al, 2013;El Ansari et al, 2015;Abraham et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…When considering students' food preferences, more than half of them consumed meat, legumes, dried fruit, dairy products and almost all bakery products every day. In studies analyzing the nutrition of university students, it was determined that the most consumed food group was cereals and grains (Bagordo, Grassi, Serio, Idolo & De Donno, 2013;El Ansari, Suominen & Samtara, 2015;Olatona et al, 2018;Rašeta et al, 2018). While some study results related to daily fruit consumption support our study findings (Yılmaz et al, 2014;El Sayed et al, 2015;Rašeta et al, 2018;Sogari et al, 2018), other studies showed that fruit consumption was found to be lower overall (Downes, 2015;El Sayed et al, 2015;Olatona et al, 2018).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation